ANALISA NIAT KEPATUHAN WAJIB PAJAK USAHA MIKRO KECIL DAN MENENGAH (UMKM) BERDASARKAN PERSEPEKTIF THEORY OF PLANNED BEHAVIOR - Dewi Fathonah Septya Rahman; Grace Widijoko (TEMA, 2022)
This study aims to determine the effect of attitude toward behavior, subjective norm, and perceived behavioral control as the intention antecedents according to the theory of planned behavior on the compliance intention of MSME taxpayers in Probolinggo Regency, and to determine the proper approach the tax officers apply based on the MSME taxpayers’ perspectives to make them aware of their tax obligations. This study employs a mixed method approach utilizing a sequential explanatory strategy. The quantitative analysis results indicated that attitude toward behavior and subjective norm had a positive and significant effect on tax compliance intentions, while perceived behavioral control had no effect on the compliance intentions of MSME taxpayers in Probolinggo Regency. Whereas, the quantitative analysis results revealing the MSME entrepreneurs’ positive response and willingness to comply, encouraged by their close persons. As for the proper approach for tax officers to apply to improve the compliance of MSME taxpayers according to their perspectives, conducting more socializations and education activities about taxation is supposed to be effective to provide the MSME entrepreneurs in Probolinggo Regency with knowledge and understanding about taxation.